Agricultural practices for growing kenaf in Iowa: II. Fiber composition and quality. (25th March 2020) - Bourguignon, Marie; Moore, Kenneth J.; Lenssen, Andrew W.; Baldwin, Brian S.
Abstract: The demand for natural fibers is increasing worldwide as markets respond to the need to replace nonrenewable sources. Kenaf ( Hibiscus cannabinus L.) is a promising biorenewable resource for producing natural fibers. Few studies have investigated the crop when grown at latitudes above 40° and in the U.S. Midwest. The objectives of this study were to assess the influence of management practices on fiber (bast and core lignocellulose) composition, carbon (C), nitrogen (N), and total ash concentration. Cultivars 'Tainung 2' and 'Whitten' were planted in Boone County, IA in 2014 and 2015 at 247, 000 or 371, 000 seed ha −1, in 38‐ or 76‐cm rows, and fertilized with N at 0, 56, 112, 168, or 224 kg ha −1 . Treatments were in a factorial design with four replications in 2 yr. Stem bast and core lignocellulose concentrations, total ash, and C/N ratio were determined at harvest. Variety or interactions of variety with management practices influenced most parameters. Increased N fertilization decreased bast cellulose concentration, but increased core cellulose concentration. Hemicellulose concentration in core was greater than in bast. Ash concentration decreased as N fertilization rate increased and interacted with seeding rate and variety. The implications of these observations are directly related to markets and desired kenaf end‐use products. Variety and management interactions influence kenaf fiber quality, and consequently are important considerations for kenaf producers and processors.